Visual evaluation of color stability after accelerated aging of pigmented and nonpigmented silicones to be used in facial prostheses - Mancuso Daniela; Goiato Marcelo; Dekon Stefan; Gennari-Filho Humberto (Wolters Kluwer Medknow Publications, 2009)
Objectives: The objective of this study was to evaluate by a visual method of comparison the color stability of nonpigmented and pigmented facial silicones after accelerated aging. Materials and Methods: Two kinds of silicones were used in this study; one specifically formulated for facial prostheses and the other an acetic silicone for industrial use. Twenty-four trial bodies were made for each silicone. These were divided into colorless and intrinsically pigmented groups: ceramic, make-up, and iron oxide. The groups were submitted to accelerated aging for nonmetallic materials. An initial reading and subsequent readings were made at 163, 351, 692, and 1000 hours using a visual method of comparison. The values were annotated in a spreadsheet by two observers, according to scores elaborated for this study. Results: All groups presented color stability in the visual method. According to the results obtained and analyzed in this study, we can conclude that both silicones, Silastic 732 RTV and Silastic MDX 4-4210, behaved similarly, they can therefore be indicated for use in maxillofacial prosthesis. The time factor of aging influenced negatively, independently of the pigmentation, or lack of it, and of silicones and no group had visually noticeable alterations in any of the accelerated aging time, independently of the addition or not of pigments.